Using a Claim-Support-Question (CSQ) Technique in Teaching and Learning English Reading for the 3rd Year English Education Students at the Department of Foreign Languages, Faculty of Education, National University of Laos: https://doi.org/10.69692/SUJMRD0901311 - PHONEKEO, Say; VONGKHAMCHANH, Sounieng; INTHAVONG, Soutta; RATTANAVONGSA, Chanmany; INTHAVONG, Khamtanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The main purposes of this study were to: 1) examine the efficiency index of reading lesson plans; 2) investigate the effectiveness index of learning reading outcomes; and 3) to study the 3rd year English education students’ satisfaction towards the teaching and learning of reading using a CSQ technique. The research instruments include four lesson plans, a pre-posttest which consists of 21 items, an observation form, and the satisfaction questionnaire, which consists of 22 items. The target group of the study was the 3rd year English education students at the Faculty of Education, National University of Laos, with a total of 28 students (23 female). The data obtained were analysed using a computer program to find the mean ( ), standard deviation (S.D), percentage (%), efficiency index (E1/E2) and effectiveness index (E.I). The findings reveal that: The efficiency index of the reading lesson plans through using a CSQ technique for the 3rd year English education students was 82.05/88.44, which is higher than the criteria of 80/80. The effectiveness index of reading learning performance through using a CSQ technique was 6699, which was equal to 66.99%, which is higher than the criteria .05 (55%). The 3rd year English education students’ satisfaction towards teaching and learning reading through using a critical thinking technique (CSQ) was at a high level ( = 4.29, S.D = 0.77).